Analisis Penggunaan Fukushi “Taihen” pada buku Minna No Nihongo - Susanti Ch. Aror (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
Adverbs (fukushi) are adverbs, not subjected to deformation. Fukushi taihen belongs to the type of Teido no Fukushi, which is an adverb that serves to express a level of state and activity. In addition to taihen, other fukushi that fall into the type of teido no fukushi include totemo, hijooni, osoroshiku, hidoku, daibu, zuibun, amarini, kanari, kekkoo, nakanaka, sukoshi, chotto, zutto, motto, masumasu. The word taihen that appears in textbooks both Minna no Nihongo 1 and 2 and Kaiwa Hyougen no Sakuin used in Kaiwa Enshuu courses is almost entirely the word taihen as an adjective. The purpose of this study was to describe the meaning of the word taihen in Japanese sentences both as adjectives and adverbs. The results of the study are as follows: (1) As an adjective, the word taihen in the sentences that are data in this study has various meanings even though at first glance it looks the same. These meanings are exhausting, difficult, troublesome, troublesome, and impractical (until it ends up being troublesome). It is from this fact that it is found that the word taihen in textbooks is more negative in tone, because of the various meanings that have been analyzed, none of them have positive nuances. (2) As an adverb (fukushi) that expresses a degree of circumstance, in general the word taihen translates to